Mathematical Literacy Based On Student’s Self-Regulated Learning by Flipped Classroom with Whatsapp Module - Ricky Fahmy, Ahmad Faridh; Sukestiyarno, Sukestiyarno; Mariani, Scolastika (Universitas Negeri Semarang, 2019)
Mathematical literacy and self regulated learning are important for students to recognize the role of mathematics in life and effectively manage student’s abilities in learning. This study aims to (1) determine the effectiveness of flipped classroom with whatsapp module on student mathematical literacy, (2) describe mathematical literacy based on self regulated learning by flipped classroom with whatsapp module. This research is mixed method type Pre-Experimental Design type One-Group Pretest-Posttest Design. The research subjects were class VII students of Al Azhar Islamic Junior high school 23 Semarang. Based on the results of the study it was obtained that flipped classroom learning with whatsapp module was effective against mathematical literacy. Students with high self regulated learning experience stabilization in mastering the seven aspects of the mathematical literacy process very well. Students with medium self regulated learning, increased in communication, representation, using symbolic, formal and technical language and operation and using mathematic, and can be mastered very well, while other aspects are well mastered. Students with low self regulated learning, increased in mastering three aspects well, namely communication, representation, using symbolic, formal and technical language and operation and using mathematic tools. On the mathematising and devising aspects of strategies for solving problems can be mastered with sufficient categories. While the reasoning and argument aspects of students are still lacking in mastering it.